International Transfer of Innovative Technologies: Prospects for Digitalization - Olga PYATAEVA; Alexey ALTUKHOV; Alexey KHARLAMENKOV; Oleg SKRYABIN; Gulmira NURGAZINA (Communications of International Proceedings, 2021)
The article discusses the main methodological provisions concerning the transfer of technologies, the essence of the transfer, the specificity of technologies as the object of transfer. The authors stress the composite nature of the technology (the right to the result of intellectual activity and the material carrier in which it is expressed). The prospects of digital transformation processes for technology transfer are considered: direction, order, possible (predicted) efficiency. The main features of network cooperation with regard to the transfer of rights and physical media are presented. Finally, a conclusion is drawn about the prospects for the digitization of technology transfer.
Keywords: Innovation; Innovation Technologies; Technology Transfer; Results of Intellectual Activity; Digital Platforms; Intellectual Property.